How Much Does I/Q Imbalance Affect Secrecy Capacity? - Boulogeorgos, Alexandros-Apostolos A.; Karas, Dimitrios S.; Karagiannidis, George K. (IEEE communications letters, 2016)
Radio frequency front ends constitute a fundamental part of both conventional and emerging wireless systems. However, in spite of their importance, they are often assumed ideal, although they are practically subject to certain detrimental impairments, such as amplifier nonlinearities, phase noise, and in-phase and quadrature (I/Q) imbalance (IQI). This letter is devoted to the quantification and evaluation of the effects of IQI on the secrecy capacity of a wiretap channel. Novel closed-form expressions are derived for the secrecy outage probability for the case of ideal transmitter and I/Q imbalanced legitimate user's and eavesdropper's receivers. Numerical results and simulations illustrate the detrimental effects of IQI on the physical layer security performance, and reveal that IQI should be seriously taken into consideration in the design of secure wireless systems.